2017
DOI: 10.1155/2017/3829340
|View full text |Cite
|
Sign up to set email alerts
|

Concrete Pavement Service Condition Assessment Using Infrared Thermography

Abstract: Infrared thermography (IRT), an effective nondestructive testing method, is used to obtain an initial evaluation of the concrete pavement surface and near surface in a time effective manner. In this paper, the effect of the depth of delamination inside concrete pavement on infrared thermography technique is studied for bridge decks inspection. To be able to mimic the delamination in subsurface, two Styrofoam cubes have been inserted in different depth near the surface of the concrete cylinder. After heating up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…However, our thermal camera, FLIR T430SC, records long-wave infrared radiation between 7 μm and 14 μm. From here, the camera calculates the temperature of the objects surface using Equation (2) [31]:…”
Section: Infrared Thermography Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our thermal camera, FLIR T430SC, records long-wave infrared radiation between 7 μm and 14 μm. From here, the camera calculates the temperature of the objects surface using Equation (2) [31]:…”
Section: Infrared Thermography Backgroundmentioning
confidence: 99%
“…In this equation, there are still several unknowns that the camera must also calculate. These are the atmospheric temperature, which is simply measured with a thermometer; the reflected temperature and emissivity, which are both calibrated for the camera before From here, the camera calculates the temperature of the objects surface using Equation (2) [31]:…”
Section: Infrared Thermography Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Pavement cracks are a common symptom and an early sign of potential damages and degradation in the pavements [1][2][3][4]. However, due to heavy traffic and drastic environmental changes, cracks can significantly affect the performance and functionality of the asphalt pavement projects and eventually lead to structural deterioration and a shortened service time.…”
Section: Introductionmentioning
confidence: 99%
“…Ptacek Lisa [20] introduced a nondestructive inspection method for concrete curing quality by near-infrared hyperspectral imaging, and the results showed that the method was highly reliable for distinguishing different curing types of concrete. Lu Yang [21] used infrared thermography to take thermal images from the surface to assess the effect of subsurface defects on the sensitivity and accuracy of detection. Jang Keunyoung [22] proposed an autonomous detection technique for concrete cracks based on deep learning by combining hybrid images of visual and infrared thermal imaging images.…”
Section: Introductionmentioning
confidence: 99%